2007
DOI: 10.1128/jvi.00219-07
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Recognition of Blood Group Trisaccharides by Norovirus

Abstract: Noroviruses are one of the major causes of nonbacterial gastroenteritis epidemics in humans. Recent studies on norovirus receptors show that different noroviruses recognize different human histo-blood group antigens (HBGAs), and eight receptor binding patterns of noroviruses have been identified. The P domain of the norovirus capsids is directly involved in this recognition. To determine the precise locations and receptor binding modes of HBGA carbohydrates on the viral capsids, a recombinant P protein of a GI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
457
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 340 publications
(479 citation statements)
references
References 32 publications
18
457
4
Order By: Relevance
“…When comparing the potential trisaccharide A and B interacting positions (343-345 and 374) (Cao et al, 2007), we found residues 344 (Val), 345 (Phe) and 374 (Pro) to be ACR in all partitions, and residue 343 to be class-specific from partition II to partition X. A second plausible binding pocket (except from the one located in the domain interface) includes residues 390-392, 395 and 344 (Cao et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When comparing the potential trisaccharide A and B interacting positions (343-345 and 374) (Cao et al, 2007), we found residues 344 (Val), 345 (Phe) and 374 (Pro) to be ACR in all partitions, and residue 343 to be class-specific from partition II to partition X. A second plausible binding pocket (except from the one located in the domain interface) includes residues 390-392, 395 and 344 (Cao et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Cao and coworkers have previously proposed from crystal structure studies that residues involved in binding of A and B trisaccharide to the P2 domain of GII.4 virus (VA387 strain), located at the dimer interface, are 343 (Ser), 344 (Thr), 345 (Arg) and 374 (Asp) from one protomer and 441 (Ser), 442 (Gly) and 443 (Tyr) in the other (Cao et al, 2007). The amino acids at the corresponding position of the first protomer in GII.3 were investigated and all found to be ACR; in chronological order: 356 (Thr), 357 (Thr), 358 (Arg) and 386 (Asp) (Fig.…”
Section: Et Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Superimposition of P2 and P1 by Dali server yields a Z score of 2.1. P2 is also homologous to the receptor binding domain of norovirus in the Caliciviridae family (Z score ϭ 2.0) (25). Noroviruses use blood-group trisaccharides as cell receptors.…”
Section: Resultsmentioning
confidence: 99%
“…The NV protruding (P) domain of the VP1 capsid protein was cocrystallized with certain saccharides of the histo-blood group antigens (HBGAs), following a proposed association of HBGA binding with viral entry into epithelial cells of the gastrointestinal tract (9). The amino acids involved in this interaction were identified, and two sites (interaction sites 1 and 2) that participate in trisaccharide A and B binding were mapped (10,11).…”
mentioning
confidence: 99%